Direct Instruction-Based Cooperative Learning Model Type Team Games Tournaments to Increase Learning Motivation and Social Attitudes - ., Yorman; Lasmawan, I Wayan; Sriatha, I Putu; Kertih, I Wayan (International Journal of Membrane Science and Technology, 2023)
This study is a quasi-experimental study using a non-equivalent post-test-only control group design as the study design, Middle school students were divided into two groups, the experimental group and the control group. Data were collected using observation sheets and questionnaires. The observation sheet was used to collect data about the application form of the direct instruction-based cooperative learning model type team games tournaments with the instilment of the local culture of Maja Labo Dahu. Moreover, questionnaires were used to collect data on learning motivation and social attitudes. The results showed that the direct instruction-based cooperative learning model type team games tournaments with the local culture of Maja Labo Dahu were significantly different from the conventional learning model in terms of learning motivation and social attitudes in students’ Social Studies learning. Based on these findings, learning using the direct instruction-based cooperative learning model type team games tournaments with the local culture of Maja Labo Dahu has a better effect on increasing learning motivation and social attitudes than the conventional learning model. About the application form.